Prophylaxis And Early Diagnosis by Cyto-immunohistochemical Evaluationin Periodontal Disease - Atena Galuscan; Liliana Vasile; Roxana Oancea; Daniela Jumanca; Angela Podariu (Romanian Society of Oral Rehabilitation, 2011)
Introduction: The inflammatory lesions in periodontal disease (PD) have a negative impact on the whole organism causing the appearance of dental infection and generating infection in the whole body. Methods: We examined 85 patients, 37 of them being diagnosed with chronic periodontal disease (confirmed by periodontogram and radiology assay) and 48 clinical healthy patients without inflammatory symptoms and loss of periodontal tissue. We performed early diagnosis and screening of PD, using salivary citodiagnosis, from sulcular liquid, and periodontal pockets using the APT-Dragan technique. Statistical analysis was made using sensibility and specificity indicators of the cytological method. Evaluation of exfoliated cells or cells obtained from tissues, allows us to obtain useful information and establish the cytology classes (C1, C2, C3, C3a, C3b). Immunohistochemical study (IHC): In order to determine immunohistochemical reactions we applied a coloring technique using monoclonal specific antibodies, which react to specific tissue antigens, on surgical obtained tissue samples. In order to establish the pathological process in chronic periodontal disease we investigated the behavior of some categories of markers: epithelial (CK) and mesenchimal (CD31). Results: The IHC study evaluated the immunologic reactivity of morphological tissues to some markers of epithelial differentiation (CK). For some of the cases, we tried to establish a correlation between the degrees of disease and the cytology class observing all clinical and radiological aspects of patients as well as interpreting cell cultures, and the results show clearly that periodontal diagnosis can be completed with cytology class diagnosis. Interpreting cytology cultures allows a correlation between the lesion grading and estimating the prognostic of disease. Conclusions: This paper sustains the idea that interdisciplinary research in PD, in order to elucidate some less known aspects of the disease is useful in order to set the basis for the early diagnosis and prognosis of PD in patients without clinical symptoms.